Hypertension in Syrian refugees: prevalence, awareness, and access to care in Denmark and Lebanon - Tala Al-Rousan; Wadih Naja; Wadih Naja; Wadih Naja; Christian Morberg Wejse; Dahlia Kaki; Michaelangelo Aoun; Michaelangelo Aoun; Michaelangelo Aoun; Saskia Lange; Laith Alshawabkeh; Rima Alhamad; et al. (Frontiers in Public Health)
BackgroundHypertension significantly contributes to global morbidity and mortality rates. Refugees are often exposed to significant risk factors that increase their chances of developing hypertension; however, the prevalence of hypertension among resettled refugees remains understudied. This study estimates and compares the prevalence of hypertension, levels of awareness, and access to care between two groups of Syrian refugees residing in humanitarian settings in Lebanon and Denmark.MethodsWe analyzed cross-sectional data collected from refugee camps in Lebanon and asylum centers in Denmark. Cluster-randomized sampling was conducted between January 2016 and December 2019. We present the estimates of hypertension prevalence, psychosocial stress, and lifestyle factors by strata, along with prevalence differences adjusted for confounding using propensity score weighting. Multiple imputation was employed to address missing data, and 95% bootstrap confidence intervals were reported.ResultsOf the 712 participants, 113 were from Denmark and 599 from Lebanon. Among them, 68% were women, and the median (IQR) age was 34 years (19). The self-reported prevalence of hypertension was 20% in Lebanon and 11% in Denmark. The prevalence of measured stage 2 hypertension was 23% in Lebanon and 24% in Denmark. The confounder-adjusted and multiple-imputed prevalence of hypertension was 5.0 (95% CI: −4.7; 16.1) percentage points higher in Denmark than in Lebanon. Among those with a known diagnosis of hypertension, only 1.6% in Lebanon and none in Denmark were currently taking medications for hypertension. The median (IQR) number of days since last seen by a medical professional was 8 days (48) in Lebanon and 8 days (21) in Denmark. The mean body mass index (BMI) was 27.0 (SD = 6.15) in Lebanon and 26.2 in Denmark (SD = 6.53). In Denmark, 50.5% reported smoking, and 23.6% reported drinking alcohol, while in Lebanon, the figures were 27.4 and 0.5%, respectively.ConclusionHypertension prevalence was found to be high among refugees, even in high-income countries (HICs) such as Denmark. Lack of access to medications in relation to self-reported prevalence was observed in both Lebanon and Denmark. Further investigation into psychosocial stress in humanitarian settings as a contributing factor to hypertension disparities in this population is crucial.